2022
DOI: 10.1016/j.jcrc.2021.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prognostic stratification using Point of Care ultrasound in critically ill COVID patients: The role of epicardial fat thickness, myocardial injury and age

Abstract: Purpose The burden of critical COVID-19 patients in intensive care units (ICU) demands new tools to stratify patient risk. We aimed to investigate the role of cardiac and lung ultrasound, together with clinical variables, to propose a simple score to help predict short-term mortality in these patients. Material and methods We collected clinical and laboratorial data, and a point-of-care cardiac and lung ultrasound was performed in the first 36 h of admission in the ICU.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Millman et al . investigated the contribution of cardiac and lung ultrasound and clinical variables by developing a straightforward point-of-care POCOVID score system to predict short-term mortality in critical COVID-19 patients [ 147 ]. They showed that deceased patients were generally older, had worse values for SOFA score, increased baseline troponin levels, reduced left ventricular ejection fraction (LVEF), impaired LV diastolic function, and increased EATth, despite a similar prevalence of severe lung ultrasound scores.…”
Section: Section 3: Eat In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Millman et al . investigated the contribution of cardiac and lung ultrasound and clinical variables by developing a straightforward point-of-care POCOVID score system to predict short-term mortality in critical COVID-19 patients [ 147 ]. They showed that deceased patients were generally older, had worse values for SOFA score, increased baseline troponin levels, reduced left ventricular ejection fraction (LVEF), impaired LV diastolic function, and increased EATth, despite a similar prevalence of severe lung ultrasound scores.…”
Section: Section 3: Eat In Clinical Practicementioning
confidence: 99%
“…The POCOVID score, including age (> 60 years), myocardial injury (LVEF < 50% or TnI > 99 th percentile), and increased EATth (> 0.8 cm), was created. The presence of two out of these three criteria identified patients with almost twice the risk of death [ 147 ].…”
Section: Section 3: Eat In Clinical Practicementioning
confidence: 99%